An impressive skeleton of the giant top predator Prestosuchus chiniquensis (Pseudosuchia: Loricata) from the Triassic of Southern Brazil, with phylogenetic remarks. (8th August 2020) - Roberto-Da-Silva, Lúcio; Müller, Rodrigo Temp; França, Marco Aurélio Gallo de; Cabreira, Sérgio Furtado; Dias-Da-Silva, Sérgio
ABSTRACT: In the present contribution, we aim to present the osteology of 'ULBRA-PVT-281', which comprises the best-preserved skeleton of Prestosuchus chiniquensis ever found. ULBRA-PVT-281 combines the morphology of two classic specimens referred to P. chiniquensis, UFRGS-PV-0156-T and UFRGSPV- 0152-T, reunited in a single operational taxonomic unit (OTU) in previous phylogenetic studies. Therefore, the new specimen reinforces the combination of both specimens. We performed a phylogenetic analysis, combining the information of these three specimens plus braincase data from a fourth specimen, UFRGS-PV-0629-T, into a new P. chiniquensis terminal taxon. Moreover, our analysis also included some new taxa potentially related to P. chiniquensis . As a result, we found a topology slightly distinct from previous studies, where Ticinosuchus ferox is the basalmost member of Loricata, which also includes the new combined P. chiniquensis . Our results place P. chiniquensis, Luperasuchus fractus, and Saurosuchus galilei distributed in a pectinate paraphyletic pattern towards Crocodylomorpha. On the other hand, a constrained analysis forcing the monophyly of these taxa demands just a single extra step. Therefore, both scenarios are plausible and agree with the placement of P. chiniquensis within Loricata, whereas T. ferox nests in Loricata only in the unconstrained analysis.